Analyzing The Coin Demonstration of The Framework of Newton’s Second Law - Küçüközer, H. A.; Küçüközer, H. (Jurnal Pendidikan Fisika Indonesia, 2023)
The study aim to show that some of the examples used in teaching Newton’s First Law in textbooks, academic studies, and platforms such as YouTube are in fact examples that comply with Newton’s Second Law. For this purpose, in the physics course, an easy-to-make "coin demonstration" from these examples was chosen. To get the data, a video of the demonstration was shot in slow-motion mode with a mobile phone. This recording was transferred to a video analysis program called Tracker and then the movement of the coin was analyzed in this program. First, the information about the coordinate planes, length, and mass required for the analysis was entered the program. Then, the position, velocity, and acceleration-time graphs of the object (coin) tracked in the uploaded video were obtained in detail. The result obtained from these analyzes is that the coin moves with acceleration. Based on this result, this study suggests that the coin example and similar examples are in accordance with Newton’s Second Law and that this should be especially considered in textbooks, academic studies, and on platforms such as YouTube.